PP.33.04: THE INFLUENCE OF BODY MASS INDEX AND METABOLIC RISK VARIABLES ON PULSE WAVE VELOCITY IN HEALTHY POPULATION. (June 2015) - Mendonca, M.; Pereira, A.; Gomes, S.; Rodrigues, R.; Sousa, A.C.; Freitas, C.; Henriques, E.; Rodrigues, M.; Ornelas, I.; Pereira, D.; Reis, R. Palma Dos
Abstract : Objective: Measurement of femoral-carotid pulse wave velocity (PWV) is recognized as a simple and practical method for assessing arterial stiffness. We determined whether the PWV of asymtomatic population with no detectable Coronary artery disease is affected by obesity and its associated metabolic risk variables. Figure. No caption available. Design and method: A cross-sectional sample of 1231 controls (26.5% female and 73.5% male), aged 30–65 years, were recruited for this study. PWV was measured by a simple automatic oscillometric technique. Adiposity measures, blood pressure, serum lipoproteins, fasting glucose were obtained. Results: The PWV of the controls was significantly higher in men (8.4 ± 1.8 m/s) than in women (7.4 ± 1.6 m/s, p < 0.0001 and increased with age in both genders specially in the female population (male r = 0.504, p < 0.0001, female r = 0.689 p < 0.0001). After being statistically adjusted for age and gender, PWV was significantly correlated with waist-to-height ratio (r = 0.235 p < 0.0001), systolic and diastolic blood pressures (r = 0.576 p < 0.0001), mean arterial pressure (r = 0.569 p < 0.0001) and fast glicose (r = 0.217). Low correlation with triglycerides, BMI (Body Mass Index), Atherogenicíndex of Plasma were found. In the multivariate regression analysis, BMI, systolic and diastolic blood pressure and age were found to be significant determinants of PWV (P < 0.001). An increasing number of clustered risk variables, including high values (75% quartiles) of Systolic and Dyastolic Pressure, BMI, waist-to-height ratio, and atherogenic index showed a graded association with PWV. Conclusions: These results suggest that obesity and its associated metabolic abnormalities are important factors in the increased PWV of healthy population and that may be useful in investigating early arterial wall changes in this population.